2002
DOI: 10.1099/0022-1317-83-10-2575
|View full text |Cite
|
Sign up to set email alerts
|

On the evolution and molecular epidemiology of the potyvirus Papaya ringspot virus

Abstract: The potyvirus Papaya ringspot virus (PRSV) is found throughout the tropics and subtropics. Its P biotype is a devastating pathogen of papaya crops and its W biotype of cucurbits. PRSV-P is thought to arise by mutation from PRSV-W. However, the relative impact of mutation and movement on the structure of PRSV populations is not well characterized. To investigate this, we have determined the coat protein sequences of isolates of both biotypes of PRSV from Vietnam (50), Thailand (13), India (1) and the Philippine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
61
0
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(68 citation statements)
references
References 27 publications
(58 reference statements)
2
61
0
5
Order By: Relevance
“…De acuerdo con Bateson et al (2002), existe variabilidad en la secuencia nucleotídica del 12% entre regiones geográficas, tales como Asia, Australia y América del Norte. Además, se ha propuesto que Asia es su centro de origen y de ahí se propagó al resto del mundo.…”
Section: Viral Genetic Diversityunclassified
See 1 more Smart Citation
“…De acuerdo con Bateson et al (2002), existe variabilidad en la secuencia nucleotídica del 12% entre regiones geográficas, tales como Asia, Australia y América del Norte. Además, se ha propuesto que Asia es su centro de origen y de ahí se propagó al resto del mundo.…”
Section: Viral Genetic Diversityunclassified
“…According to Bateson et al (2002), there is 12% of variability in the nucleotidic sequence among geographic regions such as Asia, Australia and North America. It has also been suggested that it first appeared in Asia from where it spread to the rest of the world.…”
Section: Viral Genetic Diversitymentioning
confidence: 99%
“…Higher virus disease incidence is related to greater aphid populations (Bateson et al 2002). PRSV-W control is very difficult, and the method that has been widely used is the insecticide sprays to eliminate virus vectors.…”
Section: Introductionmentioning
confidence: 99%
“…The virus is transmitted in a non-persistent manner by numerous species of aphids, including Myzus persicae and Aphis spp. (Bateson et al 2002). It has become one of the most limiting pathogens to cucurbit crops in warm climate countries as Brazil, where aphids can easily survive throughout the year.…”
Section: Introductionmentioning
confidence: 99%